Natural Autoimmunity to the Thyroid Hormone Monocarboxylate Transporters MCT8 and MCT10 - Theresa Porst; Jörg Johannes; Hans Gluschke; Richard Köhler; Sebastian Mehl; Peter Kühnen; Kostja Renko; Waldemar B. Minich; Susanna Wiegand; Lutz Schomburg (Biomedicines, 2021)
The monocarboxylate transporters 8 (MCT8) and 10 (MCT10) are important for thyroid hormone (TH) uptake and signaling. Reduced TH activity is associated with impaired development, weight gain and discomfort. We hypothesized that autoantibodies (aAb) to MCT8 or MCT10 are prevalent in thyroid disease and obesity. Analytical tests for MCT8-aAb and MCT10-aAb were developed and characterized with commercial antiserum. Serum samples from healthy controls, thyroid patients and young overweight subjects were analyzed, and prevalence of the aAb was compared. MCT8-aAb were additionally tested for biological effects on thyroid hormone uptake in cell culture. Positive MCT8-aAb and MCT10-aAb were detected in all three clinical cohorts analyzed. MCT8-aAb were most prevalent in thyroid patients (11.9%) as compared to healthy controls (3.8%) and overweight adolescents (4.2%). MCT8-aAb positive serum reduced T4 uptake in cell culture in comparison to MCT8-aAb negative control serum. Prevalence of MCT10-aAb was highest in the group of thyroid patients as compared to healthy subjects or overweight adolescents (9.0% versus 4.5% and 6.3%, respectively). We conclude that MCT8 and MCT10 represent autoantigens in humans, and that MCT8-aAb may interfere with regular TH uptake and signaling. The increased prevalence of MCT8-aAb and MCT10-aAb in thyroid disease suggests that their presence may be of pathophysiological relevance. This hypothesis deserves an analysis in large prospective studies.